De la trace au patrimoine. Archéologie de la mise en mémoire d’un quartier autoconstruit à Marseille - Karine Basset (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The self-built district known as Chieusse-Pasteur, in the 16th borough of Marseille, has undergone an original trajectory of heritagisation. It began in the early 1980s, with an urban regeneration project and culminated in 2015, twenty years afer the demolition of “Chieusse-Pasteur”, with entrance of a “trace-object”, a model of one Pasteur street’s block, at Marseille history Museum. The archeology of Chieusse-Pasteur’s memory production show how and by whom this urban heritage singularity and differents meanings attributions were constructed. At the center of trajectory, the model circulates between different spaces of memory; it highlights a debate on the trace status ; and questions nature and significance of narratives that surround it. To what extent does entrance to the museum ultimately allow former inhabitants of a disqualified habitat to claim their right to “inhabit the time”» of the city?